2007
DOI: 10.1021/np0680681
|View full text |Cite
|
Sign up to set email alerts
|

Tricalysiamides A−D, Diterpenoid Alkaloids from Tricalysia dubia

Abstract: Four rearranged ent-kaurane diterpenoid alkaloids, tricalysiamides A-D (1-4), having a cafestol-type carbon framework were isolated from the wood of Tricalysia dubia. Their absolute structures were determined on the basis of 2D NMR spectroscopy, X-ray crystallographic analysis, and chemical methods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 6 publications
0
9
0
Order By: Relevance
“…16-Demethoxydelavaine (218a and 218b) is a mixture of two regioisomers of lycoctonine-type alkaloids. 139 Four alkaloids in this group (222)(223)(224)(225) have alkoxy substituents at C-8. 135,142,143 Five new lycoctonine-type alkaloids 226-230 with an N-C-19-O-C-1 mixed acetal unit were isolated from the genera Consolida and Delphinium.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…16-Demethoxydelavaine (218a and 218b) is a mixture of two regioisomers of lycoctonine-type alkaloids. 139 Four alkaloids in this group (222)(223)(224)(225) have alkoxy substituents at C-8. 135,142,143 Five new lycoctonine-type alkaloids 226-230 with an N-C-19-O-C-1 mixed acetal unit were isolated from the genera Consolida and Delphinium.…”
mentioning
confidence: 99%
“…10 Tricalysiamides. From the wood of Tricalysia dubia collected in Okinawa, Japan, four rearranged veatchine-type C 20 -diterpenoid alkaloids with a cafestol-type diterpene framework, tricalysiamides A-D(348)(349)(350)(351), were isolated recently 222. These novel compounds are designated, after the first example, as tricalysiamide-type diterpenoids, which are characterized by the nitrogen atom being between C-3 and C-19.…”
mentioning
confidence: 99%
“…Ohwi (Rubiaceae) in 2007. 16 Cafemide A (1) was isolated as white amorphous powder, whose molecular formula was determined to be C 36 H 57 NO 4 at m/z 568.4369 [M + H] + (calcd for C 36 H 57 NO 4 + H + , 568.4360) in the HRESIMS. 1 H NMR spectrum showed the presence of one singlet methyl (δ H 0.90, s, H 3 -20), one triplet methyl (δ H 0.85, t, J = 7.0 Hz, H 3 -16′), one secondary amide (δ H 10.86, s, R−NH−CO−R′), and two olefinic methine (δ H 5.96, s, H-18 and δ H 5.47, m, H-2).…”
Section: Resultsmentioning
confidence: 99%
“…This plant species is used in traditional medicine as sedative and emetic, and for the treatment of malaria, jaundice, and skin diseases . Previous phytochemical studies of some plant species of the genus Tricalysia have reported the isolation of steroids, terpenoids, [ ] diterpenoid alkaloids, fatty acid esters, and glycosides . However, to the best of our knowledge, T .…”
Section: Introductionmentioning
confidence: 99%